FAKTOR-FAKTOR YANG MEMITIGASI FINANCIAL DISTRESS PADA PERUSAHAAN PERTAMBANGAN - Gita Wahyuningsih Putri; Wiwin Aminah (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2019)
Gross export growths in the mining sector have experienced negatively for the last few years. One of the negative impact is the reduce of revenue generated in the mining sector causing some companies gain negative profit that can trigger financial distress. This research goal is to know the effect of liquidity, activity, growth, board of directors, and audit committee give impact to the financial distress in the mining companies that listed on IDX in the period of 2011-2016. The research sample was collected by purposive sampling method in order to obtain 24 companies. Logistic regression analysis is also used to be the method of this research. The results showed that liquidity, activity, growth, board of directors and audit committee have simultaneous significant effect, but at the same time, liquidity and activities have partial significant effect to the condition of financial distress.